Profile of Wave Equation Using Boundary Condition - Akhsan, Mokhamad; Hidayat, Rusli; Pradjaningsih, Agustina (Majalah Ilmiah Matematika dan Statistika, 2016)
The wave equation is one of hyperbolic equation forms which its solution can be solved by various methods, such as Alembert and series approximation methods. Basically, the Alembert method is a coordinate transfer technique and the series approximation method is the classical separation of variable. Performance of the wave equation can be known by both of the methods with the variation of boundary conditions. The results show that both of the methods gave some equalities or differences of the profile. The different values of the velocity c ’s will have the same performance of the wave equation in the case of Dirichlet and Von Neumann boundary conditions. Calculating the profiles with a discrete version of the solution and showing some profiles at various times have been done resulting oscillation wave and moving wave.